DEFICIENCY OF DEMOCRACY IN THE EUROPEAN UNION: TO THE CONCEPT AND UNDERSTANDING OF PHENOMENOLOGY - Mykhaylo O. Baymuratov (Alfred Nobel University Journal of Law)
The article is devoted to the scientific and theoretical substantiation of the problem of democracy deficit in the European Union in the context of defining its concept and meaningful understanding of phenomenology. In domestic jurisprudence, this topic is practically not studied. The authors attribute the emergence of this issue to two factors: first, that against the background of a significant strengthening of the general trend towards deepening European integration, the content of which is the transformation of political systems of member states due to the desire to create a "stronger union" between peoples and the related phenomenon of supranationalism, there are relevant phenomena not so much destructive as improper functional in nature, which can be characterized for the EU as a "trap of democracy deficit"; secondly, the fact that a number of issues addressed by the EU, in turn, do not find a response from the citizens of this union - they are relevant and important only for EU member states, but not for the citizens of these states. Thus, it can be stated that the phenomenology of the "deficit of democracy" arises as a consequence of the apathy of EU citizens to the most important institutional and teleological issues of the association and the actual information crisis in the activities of its representative structures. Based on a systematic analysis of this phenomenology, it is concluded that the following features of this phenomenology can be distinguished: a) "democracy deficit" is a phenomenon that is not only inherent but also ordinary for modern democratic regimes (domestic level) or international organizations (international -subregional level) (subjective criterion); b) its characteristic feature is: insufficient level of democratic legitimacy (democratic recognition, recognition by the general population) of their institutions (functional- legitimate criterion); certain inconsistency of activities, mechanisms and procedures within such institutions with modern democratic standards (administrative-normative and procedural criteria). According to the author, the set of these criteria must be supplemented by a psycho-psychological criterion, which characterizes a number of features: a) the formation of individual, group and collective consciousness of citizens of EU member states to understand and perceive the values of association, order the day of its activity, the functioning of its institutional structure on a democratic basis - through personal, group and collective participation in the implementation of these tasks; b) the existence of its own, group, collective system of interests in relation to the EU and its activities and the appropriate positioning on their implementation through the appropriate individual, group and collective involvement in their solution; c) formation of the corresponding European legal consciousness on the basis of perception of European values, involvement in processes of their realization through a prism of activity of institutional structure of integration association. It is concluded that the phenomenon of "democracy deficit" is not so much an indicator of lack and neglect of democratic principles within the EU, as a sign of lack or imperfection of democratic procedures in political decision-making institutions of the integration association in the context of participation of citizens of its member states. developing and making such decisions. It is noted that the active doctrinal search for representatives of the science of European law and EU law led to the conclusion that overcoming the phenomenology of the "deficit of democracy" is impossible without developing and optimizing the interaction of federalism and democracy within the integration association. the whole "European integration project". Emphasis is placed on overcoming the phenomenology of the "democracy deficit" by objectifying and intensifying the system of communicative interaction of residents of territorial communities of EU member states in the context of developing forms of direct democracy, including new forms of democratic human participation in discussions and decision-making. local, regional self- government, as well as at the national and supranational levels.